Traffic Police Management to support Security, Safety, Order and Smoothness (Kamseltibcar Lantas) in DKI Jakarta Province, Indonesia - Bakharuddin Muhammad Syah (Jurnal Syntax Admiration, 2024)
The work of police as an institution is clear, to ensure safety, balance, order, and justice in a society. This paper will dive into the role of traffic police management and community policing to ensure order in DKI Jakarta. Policemen in Jakarta have different roles and different targets to achieve, some work to ensure justice is served to criminals and perpetrators by conducting investigations on reports. Some oversee daily lives of civilians in the province by ensuring traffic laws are being obeyed, and other activities that involve the lives of civilians. This concept is more recognized as community policing. In this study, qualitative methods through data collection and interviews are used in the research methods. Public and community transportation will also be taken into consideration as one of the concepts in the study as it is used as the theoretical lens.